1997
DOI: 10.1136/bmj.315.7110.713
|View full text |Cite
|
Sign up to set email alerts
|

Rising incidence of insulin dependent diabetes in children aged under 5 years in the Oxford region: time trend analysis

Abstract: Incidence of insulin dependent diabetes in children aged under 5 years has risen markedly in the Oxford region over the past decade. The cause of the increase is unknown, but environmental influences encountered before birth or in early postnatal life are likely to be responsible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
147
10
5

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(195 citation statements)
references
References 22 publications
33
147
10
5
Order By: Relevance
“…In contrast to reports from Europe [2], Oxford, UK [5] and Finland [6], in which higher rates of increase in the youngest age group have been documented, a disproportionate rate of increase in 0 to 4-year-olds was not found in Western Australia. There was no significant difference in the incidence rate trends between the age groups, which is similar to the findings in other countries, including Scotland [25,26].…”
Section: Discussioncontrasting
confidence: 92%
“…In contrast to reports from Europe [2], Oxford, UK [5] and Finland [6], in which higher rates of increase in the youngest age group have been documented, a disproportionate rate of increase in 0 to 4-year-olds was not found in Western Australia. There was no significant difference in the incidence rate trends between the age groups, which is similar to the findings in other countries, including Scotland [25,26].…”
Section: Discussioncontrasting
confidence: 92%
“…Our results indicate that caution should be exercised when extrapolating regional differences in incidence of childhood onset Type 1 diabetes to differences in lifelong risk for the disease. To decide whether the higher and increasing incidence rates of childhood Type 1 diabetes in certain countries are due to earlier disease presentation [1,8,9,10] or to an overall increased lifelong risk when compared to countries with lower incidence rates of childhood Type 1 diabetes, it would be necessary to compare incidence rates across countries over even larger age-ranges and longer observation periods.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of the disease in children up to 15 years of age is well documented by two multi-centre studies [4,5,6,7], with incidence varying from less than 1 per 100000 person years in Venezuela and China to more than 35 per 100000 person years in Finland and Sardinia. Furthermore, recent studies suggest a higher rate of increase in disease among children younger than 5 years than in children between 5 and 15 years of age [8,9,10,11], although other studies have not observed a differential rise in incidence [12,13,14].…”
mentioning
confidence: 97%
“…In the United States and Western Europe, the current incidence rate for type 1 diabetes is second only to that of bronchial asthma in terms of the severe chronic diseases of childhood. Several European countries such as the United Kingdom and Finland have experienced more than a doubling in incidence of 'classical' type 1 diabetes over the past three decades [14,15]. In contrast, Asian countries including Japan, Korea and China have a low incidence.…”
Section: Epidemiology Of Type 1 Diabetes In Japanmentioning
confidence: 99%